Of volcanoes and insects: the impact of the Puyehue–Cordon Caulle ash fall on populations of invasive social wasps, Vespula spp. Issue 2 (16th December 2012) - Masciocchi, M.; Pereira, A. J.; Lantschner, M. V.; Corley, J. C.
Abstract: Volcanic eruptions have important effects on terrestrial ecosystems. The biotic effects of volcanic ash on insect populations vary from widespread and catastrophic to subtle and localized. Volcanic eruptions may increase insect mortality through the effects of the ash plume, and these vary by taxon or specific biological features. The Puyehue – Cordon Caulle Volcanic Complex is the most recent eruption in Patagonia. Here we explore and describe the effects of the eruption of this volcanic complex on invasive Vespula spp. populations. These wasps are very abundant social hymenoptera that have recently invaded Patagonia. We placed baited traps following the gradient of deposited ash, and revisited them once a week during February to April. No wasps were caught where ash deposition levels exceeded 3.0 cm. The number of wasps caught in sites with minimal ash deposits was similar to that of previous years. In locations where ash layers are intermediate, a few wasps were observed, but only during the peak of wasp abundance. We show that Vespula spp. populations were severely affected by the ash deposition and plume, caused by this eruption. These results show catastrophic effects of ash deposition over a large area, even at great distances from the eruption epicenter. We conclude that wasp mortality explained by the volcanic eruption may reach distant areas, and cause local extinction. In areas where active volcanoes are common, invasive insects may encounter an additional obstacle in their invasion success.